БЕРЕГОВАЯ МОРФОСИСТЕМА КАК ОБЪЕКТ ГЕОМОРФОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ - Игнатов Е.И. (My University, 2005)
The paper deals with theoretical fundamentals of morphosystem analysis application for land-sea contact zone investi-gation. Coastal morphosystem with three subsystems - primor'e, coastal zone, and vzmor'e - were taken as the objects. Authors suggest meaning the term "coastal morphosystem" as the unity of coastal zone and adjacent parts of pri-nor'e and vzmor'e, which exchange energy and matter in the course of recent relief formation.
Keywords: 551.435.3